Advanced Development Strategies Of Offshore Places At PT Emgl's Offshore Fields Using Optimization Simulation Models - Imam Ahmad Firdaus; Arief Bimantoro Suharko (Jurnal Scientia, 2024)
The oil and gas industry in offshore areas in Indonesia has developed since the 1970s. Based on information from SKK Migas, there are 634 platforms in Indonesian territory spread from Sumatra to Eastern Indonesia, and approximately 100 of them are no longer in production (Speight 2015; Utomo 2012; Wiratno 2021). The existence of offshore platforms that are not utilized creates problems for KKKS both in terms of operations and the environment. Therefore, it is necessary to use a further management related to the existing platforms in the Indonesian sea. This research is descriptive - analytic in a case study at the company PT EMGL using qualitative and quantitative approaches to obtain the optimal scenario in planning the further development of offshore platforms in the Offshore A field. Data collection methods are interviews and literature studies. After obtaining data related to the condition of Offshore A Field, the cost range for reactivation and demolishing costs for each platform is calculated and the potential hydrocarbon resources in it are calculated. This model is then simulated in the calculation of net cash flow in the Monte Carlo simulation. The results of the Monte Carlo simulation regarding the possible scenarios that occur in 10,000 iterations show a convergent range of results in terms of 3 central tendency parameters, which are mean, median and mode (Holt and Scariano 2009). In this study, the Monte Carlo Simulation gives a convergent NPV value. This parameter is used as an economic evaluation of the project which can be used as an initial method for determining further development strategies. This value can be regarded as a quantification of opportunities or risks as a basis for decision making.